DESCRIPTIVE ANALYSIS OF TRANSLATION METHODOLOGY FOR IATE ECOLOGY TERMS IN GEORGIAN - Zeinab Gvarishvili; Zhuzhuna Gumbaridze; Lia Davitadze; Shota Rodinadze (International Journal of Innovative Technologies in Social Science, 2024)
This article examines key terminological challenges when translating ecological terms from English into Georgian, within the framework of the "Terminology without Borders" (TWB) project, initiated by the Directorate-General for Translation (DG TRAD) of the European Parliament. This study contributes to the IATE (InterActive Terminology for Europe) database, aiming to enhance communication in the environmental domain by adapting EU terminology to meet citizens’ needs worldwide. The paper underscores the importance of terminological consistency in ensuring translation clarity and precision. Specifically, it documents and provides a descriptive analysis of four terms, identifying linguistic cases of polysemy, synonymy, and term variation, commonly observed across all 102 ecological terms in the database. The introductory section provides a comprehensive overview of the historical development of terminography in Georgia, examining its evolution over time, as well as the contemporary challenges it faces in the field. The core of the study is dedicated to a procedural analysis of terms: industrial crop, primary production waste, green waste, and corn salad. The analysis includes reviewing term definitions, identifying term domains, exploring contextual meanings, detecting target-language equivalents, and corpus-based examination of each term. This approach is designed to systematically address terminological challenges within the context of IATE, thus improving the reliability of the Georgian entries for environmental terminology. A secondary objective is to evaluate the effectiveness of IATE as a resource for translating ecological terminology based on English source texts, highlighting potential areas for improvement in multilingual database management. The concluding section summarises the findings, emphasizing that terminological consistency is fundamentally dependent on the clarity and precision of source texts, especially within specialized domains such as the environment.